Thai-textual Cyberbullying Detection using Support Vector Machines - Jenkarn, Nuttakit (Science Technology and Innovation Journal, 2020)
This research applied data mining and machine learning to develop a prototype “Thai-textual Cyberbullying Detection using Support Vector Machines” that can be future online Cyberbullying social media detection. Support Vector Machines (SVMs), K-Nearest Neighbour and Naïve Bayes are selected to use in our research. From the evaluation by Confusion Matrix, SVMs had the highest classification accuracy as 83.91